2019
DOI: 10.1073/pnas.1820175116
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical candidate for the treatment of visceral leishmaniasis that acts through proteasome inhibition

Abstract: Visceral leishmaniasis (VL), caused by the protozoan parasites Leishmania donovani and Leishmania infantum, is one of the major parasitic diseases worldwide. There is an urgent need for new drugs to treat VL, because current therapies are unfit for purpose in a resource-poor setting. Here, we describe the development of a preclinical drug candidate, GSK3494245/DDD01305143/compound 8, with potential to treat this neglected tropical disease. The compound series was discovered by repurposing hits from a screen ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
193
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(198 citation statements)
references
References 20 publications
5
193
0
Order By: Relevance
“…Fubinaca/Cannabinoid receptor 1 (PDB:6N4B, EMD:0339) 33 ; GSK 3494245/Leishmania 20S proteasome (PDB:6QM7, EMD:4590) 36 ; Paromomycin/Leishmania ribosome (PDB:6AZ1, EMD:7024) 35 ; Menthol analogue WS-12/Ion channel TRPM8 (PDB:6NR2, EMD:0488) 41 ;…”
Section: Methodsmentioning
confidence: 99%
“…Fubinaca/Cannabinoid receptor 1 (PDB:6N4B, EMD:0339) 33 ; GSK 3494245/Leishmania 20S proteasome (PDB:6QM7, EMD:4590) 36 ; Paromomycin/Leishmania ribosome (PDB:6AZ1, EMD:7024) 35 ; Menthol analogue WS-12/Ion channel TRPM8 (PDB:6NR2, EMD:0488) 41 ;…”
Section: Methodsmentioning
confidence: 99%
“…That said, new therapies are urgently needed given the lack of effective vaccines, drug resistance, limited efficacy and toxicity associated with current treatment (2)(3)(4). Given that the UPS pathway is essential for cell survival, inhibition of the proteasome has emerged as an attractive anti-parasitic target (5)(6)(7)(8)(9). However, the regulation of UPS-mediated protein degradation in clinically important protozoans remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed the potential for proteasome inhibition as a treatment for three diseases caused by trypanosomatid parasitic protozoa, including leishmaniasis [9,10]. The proteasome is dependent on the ubiquitination pathway to identify substrates for degradation and a search of the Leishmania genome reveals a range of E1, E2 and E3 ligases, as well as a number of DUBs [33].…”
Section: Discussionmentioning
confidence: 99%
“…Reversible post-translational modification (PTM) of proteins with chemical groups, such as phosphorylation, or other proteins, such as ubiquitination, are likely to be pivotal for successful life cycle progression [35] and intracellular parasitism. In addition, irreversible PTM such as proteolytic cleavage is important for the cellular remodeling that occurs during the life cycle of Leishmania and the commitment to differentiation [68], as well as in amastigote survival [9,10].…”
Section: Introductionmentioning
confidence: 99%